MOBILITY AND PROXIMITY COEFFICIENT TO HIGH-TRAFFIC VOLUME IN DAILY SCHOOL OPERATIONS - Mohd Yusoff, Zaharah; Aziz, Intan S.; Naharudin, Nabilah; Abdul Rasam, Abdul Rauf; Ling, Oliver Hoon Leh; Nasrudin, Na’asah (PLANNING MALAYSIA, 2022)
Heavy traffic volume especially in peak time led to bigger issue during daily school operating time. Drivers’ behaviours are often seen as the central cause to the increased number of road accidents around school, particularly during morning hours when accompanying adults are in a rush to office. Good accessibility and connectivity are the main consent in a school planning guideline. However, the proximity to major roads results in a higher level of traffic around the school. The research hypothesis is to investigate whether the proximity distance playing a significant role in determining mobility choice to school. The Geographical Information System software was used to analyse the safety measures such as distance, coverage area and routes to school, while the mobility analysis is done using the SPSS. 553 samples of questionnaires have been distributed at six identified schools in Johor Bahru. The result from analysis shows 79.39% of children use motorised vehicle thus, contributing to poor traffic flow during peak hour. While in comparing the coverage of each school to the guidelines, 99.45% of children’s houses are within the accepted radius distance. The findings of this study will highlight to some poor driving habits among parents, which are a major contributor to the heavy traffic flow surrounding schools.